PTU-017 The Use Of Small Bowel Capsule Endoscopy In The Octogenarians Group; The Edinburgh Experience. (9th June 2014) - Bartzis, L; Koulaouzidis, A
Abstract : Introduction: Over the last 13 years, the clinical use of capsule endoscopy (CE) has revolutionised the investigation pathways for the small-bowel. Although non-invasive (as procedure), there are reports of capsule aspiration in certain patient-groups. 1 Moreover, CE video review is a time-consuming process and – on occasions – with limited diagnostic yield (DY). There is scarcity of data on the use of CE in octogenarians. 2–4 We aim to report our centre experience in using CE in octogenarians. Methods: Retrospective study; the SBCE data base of our unit was interrogated for patients >80 years of age who underwent CE. Categorical data are reported as mean ±SD. The Fischer's exact, the chi-square and the t (unpaired) tests were used to compare datasets. A two-tailed P value of <0.05 was considered statistically significant. Results: 1, 477 patients underwent small-bowel CE between 2005 and 2013. 93 CE were performed in 84 (35M/59F) octogenarians; mean age 84 ± 2.9 years. PillCam ® SB1/SB2 and MiroCam ® were used in 61 and 32 CE examinations, respectively. Ten (11.9%) patients had more than 1 CE. One patient was unable to swallow the capsule, and in another the capsule was retained in the stomach. The CE report was unavailable in one case. Indications for small-bowel CE were IDA: 44, OGIB: 29, OBIG+IDA: 6, diarrhoea 4, small-bowel varices: 1. Forty-five (53.6%) patients subsequently died. The mean time from SBCE to death was 23 months (SD 20.9, range: 0.13–83 months). The DY (all findings) of CE in our octogenarian cohort was 56.8%. Vascular lesions (any P class)/active bleeding were found in 33, inflammatory pathology in 9, and other in 4 CE. No neoplastic pathology was identified. The DY was independent to the indications for the procedure ( P = 0.166), the small-bowel CE system used ( P = 0.068), the patient final outcome i.e. deceased/alive ( P = 0.051) and/or the time from CE to death ( P = 0.053). Conclusion: CE in patients >80 years of age has high DY, but sinister pathology in this cohort is rare. Furthermore, small-bowel CE has limited impact on the final patient outcome in this patient group. References: Koulaouzidis A, et al . Small-bowel capsule endoscopy: a ten-point contemporary review. World J Gastroenterol 2013;19:3726–46 Koulaouzidis A, et al . The use of small-bowel capsule endoscopy in iron-deficiency anemia alone; be aware of the young anemic patient. Scand J Gastroenterol 2012;47:1094–100 Tsibouris P, et al . Capsule endoscopy findings in patients with occult or overt bleeding older than 80 years. Dig Endosc 2012;24:154–8 Sidhu R, McAlindon ME. Age should not be a barrier to performing capsule endoscopy in the elderly with anaemia. Dig Dis Sci 2011;56:2497–8 Disclosure of Interest: None Declared.